Immunoexpression of Ki-67 in determining prognosis of oral cavity squamous cell carcinoma - Kintawati, Silvi; Pramesti, Hening Tjaturina (Padjadjaran Journal of Dentistry, 2019)
Introduction: Several researchers have been stated that the right prognosis of oral squamous cell carcinoma (OSCC) can be achieved through assessment of tumor clinical staging and tumor histopathological grading as well. The use of biomarker in histopathological grading is obviously helpful to ensure the prognosis. Objective of this study was to determine the correlation between expression of Ki-67 and histopathological grading of OSCC. Methods: A retrospective study was conducted by assessing 20 cases of paraffin-embedded OSCC derived from the Department of Pathology Anatomy of Hasan Sadikin Hospital Bandung in 2013. The OSCC performing was stained by hematoxylin-eosin. While, antibodies Ki-67 was used in immunohistochemistry reaction to determine the relation of expression of Ki-67 with histopathologic grade of OSCC for predicting a prognosis. Results: The result show that distribution of Ki-67 expression were vary from 20% to 80% in each case. Ki-67 intensity was also distributed from weak, moderate and strong. Conclusion: There is a significant correlation between Ki-67 immunoexpression and the histopathological grading of squamous cell carcinoma (p < 0.01), thus, Ki-67 can be used to predict a prognosis.Keywords: Immunoexpression, Ki-67, prognosis, oral cavity squamous cell carcinoma